2016
DOI: 10.5966/sctm.2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-Grade Isolated Human Kidney Perivascular Stromal Cells as an Organotypic Cell Source for Kidney Regenerative Medicine

Abstract: Mesenchymal stromal cells (MSCs) are immunomodulatory and tissue homeostatic cells that have shown beneficial effects in kidney diseases and transplantation. Perivascular stromal cells (PSCs) identified within several different organs share characteristics of bone marrow‐derived MSCs (BM‐MSCs). These PSCs may also possess tissue‐specific properties and play a role in local tissue homeostasis. We hypothesized that human kidney‐derived PSCs (hkPSCs) would elicit improved kidney repair in comparison with BM‐MSCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 40 publications
2
54
1
Order By: Relevance
“…The composition of this latter layer is primarily controlled by resident tissue fibroblasts, that act as a signaling hub for tissue homeostasis and repair. Like the endothelium, they have an organ‐specific phenotype where anatomical localization is related to the specific transcriptome profiles, such as embryonic patterning genes, as well as function . While these cells intimately communicate with tissue cells and the immune system to preserve an anti‐inflammatory and trophic milieu, they can respond to injury by differentiating into proliferating myofibroblasts and eventually converting into a nonproliferating, matrix‐producing phenotype.…”
Section: The Concept Of Bidirectional Angiocrine Signaling In Tissue mentioning
confidence: 99%
“…The composition of this latter layer is primarily controlled by resident tissue fibroblasts, that act as a signaling hub for tissue homeostasis and repair. Like the endothelium, they have an organ‐specific phenotype where anatomical localization is related to the specific transcriptome profiles, such as embryonic patterning genes, as well as function . While these cells intimately communicate with tissue cells and the immune system to preserve an anti‐inflammatory and trophic milieu, they can respond to injury by differentiating into proliferating myofibroblasts and eventually converting into a nonproliferating, matrix‐producing phenotype.…”
Section: The Concept Of Bidirectional Angiocrine Signaling In Tissue mentioning
confidence: 99%
“…Human kidney-derived perivascular stromal cells (hkPSCs) were isolated from transplant-grade kidneys discarded for as surgical waste. 35 fluorescence-activated cell sorting (FACS) confirmed that homogeneous NG2-positive hkPSC populations between passages 4 and 8 and hMVEC between passages 6 and 8 were cultured in EC-SFM full medium at 37 C and 5% CO 2 as described in detail previously. 34…”
Section: Human Kidney-derived Perivascular Stromal Cells Culturementioning
confidence: 99%
“…RNA isolation was achieved using an RNeasy mini kit (Qiagen, Hilden, Germany), and quantitative polymerase chain reaction (qPCR) was performed as previously described. 35 Forward and reversed VWF, KLF2, and MCT1 primer sequences are depicted in Table 1. Ct values were normalized by the Ct of GAPDH.…”
Section: Rna Isolation and Qpcrmentioning
confidence: 99%
“…This enhanced wound repair was mediated through hepatocyte growth factor release. Moreover, kPSCs ameliorated kidney injury in a mouse model of acute kidney injury 15 . Therefore, kPSCs seem to have superior renal repair capacities and are an interesting new source for cell therapy in kidney diseases.…”
Section: Introductionmentioning
confidence: 97%
“…Perivascular stromal cells can also be isolated from the mouse 12 13 14 and human kidney 15 16 . We extensively characterized kPSCs and compared these to bmMSCs.…”
Section: Introductionmentioning
confidence: 99%